History Teaching, Thinking Development, and Transforming Society - Reyes, Wensley M (SUSURGALUR, 2014)
ABSTRACT: History teaching is defined as the transmission of historical knowledge to people who do not yet have such knowledge. As a discipline, history concerns itself with a scientific study of the past. In the age of globalization, there is a need to reassess the way schools perceive and approach the subject and teaching of history, especially when it has become part of what we call âservice coursesâ â subjects in our schools that exist in order to satisfy the requisites of the implementing educational agency. Historical knowledge, with the current trends in education, has been contested. Also teaching history within the classroom has been challenged due to the question of practicality of historical knowledge. Some cynics argued that historical knowledge will not provide much help, especially in solving pressing issues and problems. This assumption about historyâs impractical knowledge resulted to the relegation of the study of the past to the margins. Likewise, teaching history has not merited the prestige of the so-called âusable subjectsâ. Thus, rethinking historyâs practicality and the usability of such knowledge should be incorporated with the teaching of the subject. KEY WORD: History, history teaching, development, school, society, service courses, usable subjects, and rethinking history.IKHTISAR: âPengajaran Sejarah, Perkembangan Berpikir, dan Transformasi Masyarakatâ. Pengajaran sejarah didefinisikan sebagai transmisi pengetahuan sejarah kepada masyarakat dari yang belum tahu menjadi tahu. Sebagai sebuah disiplin ilmu, sejarah hirau dengan masalah kajian ilmiah pada masa lalu. Di era globalisasi, ada kebutuhan untuk menilai kembali cara sekolah memahami dan mendekati subjek dan pengajaran sejarah, terutama ketika telah menjadi bagian dari apa yang kita sebut âprogram layananâ â dimana mata pelajaran yang ada di sekolah kita untuk memenuhi syarat dari lembaga pelaksana pendidikan. Pengetahuan sejarah, dengan kecenderungan saat ini dalam pendidikan, telah dipertaruhkan. Juga mengajar sejarah didalam kelas telah ditantang karena masalah kepraktisan pengetahuan sejarah. Beberapa yang sinis berpendapat bahwa pengetahuan sejarah tidak akan memberikan banyak bantuan, terutama dalam memecahkan berbagai masalah dan isu yang mendesak. Asumsi tentang pengetahuan sejarah yang kurang praktis ini mengakibatkan degradasi studi masa lalu yang terpinggirkan. Karenanya, mengajar sejarah belum memiliki kelayakan prestise yang disebut "mata pelajaran siap-pakai". Jadi, memikirkan kembali pengetahuan sejarah yang praktis dan berguna harus dimasukkan dalam pengajaran sejarah.KATA KUNCI: Sejarah, pengajaran sejarah, pembangunan, sekolah, masyarakat, program layanan, pelajaran yang berguna, dan memikirkan kembali sejarah.About the Author: Assist. Prof. Wensley M. Reyes is currently a faculty member of the Faculty of Behavioral and Social Sciences PNU (Philippine Normal University) in Manila, the Philippines. He has earned from the University of the Philippines â Diliman his bachelorâs and masterâs degrees in the discipline of History in 2002 and 2010 respectively. His e-mail address is: reyes.wm@pnu.edu.phHow to cite this article? Reyes, Wensley M. (2014). âHistory Teaching, Thinking Development, and Transforming Societyâ in SUSURGALUR: Jurnal Kajian Sejarah & Pendidikan Sejarah, Vol.2(2), September, pp.171-178. Bandung, Indonesia: Minda Masagi Press and UBD Bandar Seri Begawan, Brunei Darussalam, ISSN 2302-5808.Chronicle of the article:Â Accepted (August 14, 2014); Revised (September 2, 2014); and Published (September 24, 2014).